EXPERIMENTAL INVESTIGATION OF COORDINATION AT AGGREGATE VERSUS INDIVIDUAL LEVEL - Chytilova, Helena (European Scientific Journal, ESJ, 2015)
We argue that the ability to coordinate under strategic complementarity is substantially affected by mutual interactive development at the individual and aggregate level. Optimal strategy which is followed by each player does not only depend upon strategy of the other player but also on conditions prevailed at the aggregate level. Results of our laboratory experiment suggest that certain type of player might be or might be not awarded depending on type of the economy, which has important implications at the aggregate level with respect to the speed of the convergence.